2021
DOI: 10.20473/amnt.v5i4.2021.395-407
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Carbohydrate Counting in Type 1 Diabetes Mellitus : A Scoping Review

Abstract: Asupan karbohidrat merupakan penentu utama kestabilan kadar glukosa pasien dengan DM tipe 1. Carbohydrate counting sebagai teknik pengaturan diet pasien dengan DM tipe 1 diketahui memiliki fleksibilitas dalam kontrol glukosa darah melalui pengaturan jumlah asupan karbohidrat dan dosis insulin, namun tetap dibutuhkan pemahaman yang baik terkait praktik carbohydrate counting agar tercapai target kontrol glukosa darah. Tujuan: Artikel ini bertujuan mereview hasil penelitian sebelumnya terkait manfaat terhadap kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…13 However, CC is a complex skill that is subject to error among children and young adults with T1DM and their families. 16 Therefore, identifying opportunities to develop CC skills can improve interventions and achieve accurate CC by patients and improved glycaemic management. 16 Few studies have investigated CC knowledge among individuals with T1DM in SA.…”
Section: What This Study Addsmentioning
confidence: 99%
See 3 more Smart Citations
“…13 However, CC is a complex skill that is subject to error among children and young adults with T1DM and their families. 16 Therefore, identifying opportunities to develop CC skills can improve interventions and achieve accurate CC by patients and improved glycaemic management. 16 Few studies have investigated CC knowledge among individuals with T1DM in SA.…”
Section: What This Study Addsmentioning
confidence: 99%
“…16 Therefore, identifying opportunities to develop CC skills can improve interventions and achieve accurate CC by patients and improved glycaemic management. 16 Few studies have investigated CC knowledge among individuals with T1DM in SA. A pilot study conducted with 94 Emirati and Omani adults with diabetes showed low scores for knowledge of the carbohydrate content of foods.…”
Section: What This Study Addsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes mellitus (DM) is a metabolic disorder characterized by elevated levels of blood glucose (BG) due to compromised insulin secretion, impaired insulin action, or a combination of both [ 1 ]. Based on the presence or absence of insulin, diabetes mellitus can be classified into two primary groups: type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%